Kids Feeling Good about Being Indigenous at School and Its Link to Heightened Educational Aspirations - Peacock, Huw; Guerzoni, Michael (My University, 2022)
Aspiration formation is an important milestone in the cognitive and personal development of children, influential in directing their life pursuits entering adulthood. Educational aspirations are particularly prized, and subsequently nurtured, within Western societies. For Indigenous children, connection to, embrace of, and security in one’s indigeneity has been shown to be conducive to more favorable maturation, educational outcomes, and emotional and physical well-being. This chapter employs quantitative data from the Longitudinal Study of Indigenous Children Wave 8 K cohort to examine how cultural identity influences the secondary school completion aspirations of 499 Aboriginal and Torres Strait Islander and/or Torres Strait Islander children aged 10.5–12 years. The authors find that Indigenous children who are comfortable in their indigeneity, particularly in the classroom, are more likely to desire to complete their secondary education. These findings support the need for further awareness and more support by teachers of Indigenous children.
The Oxford Handbook of Indigenous Sociology
Keywords: Adolescents and youth; Childhood and child development; Culture and language; Health and wellbeing; Identity; Social engagement